Altered plasma versus vascular biopterins in human atherosclerosis reveal relationships between endothelial nitric oxide synthase coupling, endothelial function, and inflammation. - Antoniades, C; Shirodaria, C; Crabtree, M; Rinze, R; Alp, N; Cunnington, C; Diesch, J; Tousoulis, D; Stefanadis, C; Leeson, P; Ratnatunga, C; Pillai, R; et al. (2007)
BACKGROUND: Tetrahydrobiopterin (BH4) is a key regulator of endothelial nitric oxide synthase (eNOS) activity and coupling. However, the extent to which vascular and/or systemic BH4 levels are altered in human atherosclerosis and the importance of BH4 bioavailability in determining endothelial function and oxidative stress remain unclear. We sought to define the relationships between plasma and vascular biopterin levels in patients with coronary artery disease and to determine how BH4 levels affect endothelial function, eNOS coupling, and vascular superoxide production. METHODS AND RESULTS: Samples of saphenous veins and internal mammary arteries were collected from 219 patients with coronary artery disease undergoing coronary artery bypass grafting. We determined plasma and vascular levels of biopterins, vasomotor responses to acetylcholine, and vascular superoxide production in the presence and absence of the eNOS inhibitor N(G)-nitro-L-arginine methyl ester. High vascular BH4 was associated with greater vasorelaxations to acetylcholine (P<0.05), whereas high plasma BH4 was associated with lower vasorelaxations in response to acetylcholine (P<0.05). Furthermore, an inverse association was observed between plasma and vascular biopterins (P<0.05 for both saphenous veins and internal mammary arteries). High vascular (but not plasma) BH4 was associated with reduced total and N(G)-nitro-L-arginine methyl ester-inhibitable superoxide, suggesting improved eNOS coupling. Finally, plasma but not vascular biopterin levels were correlated with plasma C-reactive protein levels (P<0.001). CONCLUSIONS: An inverse association exists between plasma and vascular biopterins in patients with coronary artery disease. Vascular but not plasma BH4 is an important determinant of eNOS coupling, endothelium-dependent vasodilation, and superoxide production in human vessels, whereas plasma biopterins are a marker of systemic inflammation.